2020
DOI: 10.1002/cssc.202002467
|View full text |Cite
|
Sign up to set email alerts
|

Designer Ferrocene Catholyte for Aqueous Organic Flow Batteries

Abstract: The aqueous organic flow battery (AOFB) holds enormous potential as an energy storage device for fluctuating renewable electricity by exploiting the redox reactions of water‐soluble organic molecules. The current development is impeded by lack of organic molecules adequate as catholyte, yet how the catholyte structure impacts the battery lifetime remains unexplored. Here, six ferrocene derivatives with deliberately tuned chemical structure were devised. They underwent reversible redox reactions in water, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 33 publications
1
56
0
Order By: Relevance
“…In the past ten years, significant progress has been made in the aqueous organic redox flow battery (AORFB) technology. 1–5 Water-soluble viologen (anolyte), 6–10 quinone (anolyte and catholyte), 11–16 phenazine (anolyte), 17–20 TEMPO (catholyte), 21–25 and ferrocene (catholyte) 7,10,26,27 compounds were developed for AORFB demonstration. However, the most critical roadblock to further boost the energy storage performance of AORFBs lies in the lack of stable catholyte materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past ten years, significant progress has been made in the aqueous organic redox flow battery (AORFB) technology. 1–5 Water-soluble viologen (anolyte), 6–10 quinone (anolyte and catholyte), 11–16 phenazine (anolyte), 17–20 TEMPO (catholyte), 21–25 and ferrocene (catholyte) 7,10,26,27 compounds were developed for AORFB demonstration. However, the most critical roadblock to further boost the energy storage performance of AORFBs lies in the lack of stable catholyte materials.…”
Section: Introductionmentioning
confidence: 99%
“…7 Subsequent studies revealed that the derivatives of C 1 -FcNCl with a longer methylene chain between the Fc and ammonium groups displayed improved cycling performance. 10,27 One argument was that C 1 -FcNCl might undergo a dimerization decomposition mechanism. 10 Instead, Cp − ligand exchange with an external ligand such as Cl − was proposed as a possible degradation pathway for ferrocenium cation (Fc + ) in organic solutions in 1972.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the substituent chain lengths on cationic ferrocene molecules was thoroughly studied in [162], showing that both the solubility and stability of the ferrocene derivative is related to the localized LUMO density on ferrocene. The most stable BQH−Fc, which has the lowest LUMO density on Fe, provided a high capacity retention rate of 99.993% h −1 at 1.5 mol/L concentration.…”
Section: Metal Complex-high-spin (Ferrocenes)mentioning
confidence: 99%
“…TEMPO is a stable nitroxide radical that can donate 1 e − to form an oxoammonium cation. Its first application in neutral AORFBs was in the form of 4-hydroxy-2,2,6, [15] Copyright 2021, Wiley-VCH.…”
Section: Nitroxide Radicalsmentioning
confidence: 99%
“…Yang et al prepared six derivatives with deliberately tuned molecular structures and compared them under identical operational conditions in full flow cells (Figure 3a). [15] The experimental results, along with density functional theory (DFT) calculations, suggest that the higher density of the lowest unoccupied molecule orbital (LUMO) on Fe (III) may exacerbate the attack of nucleophiles on the iron center and, consequently, lead to fast capacity decay (Figure 3b,c). They selected the most stable derivative, bis((6trimethylammonio)-hexyl)-ferrocene dibromide (BQH-Fc), and tested it with BTMAP-Vi in a 1.5 m high concentration battery.…”
Section: Organometallicsmentioning
confidence: 99%